Postcolonial, post-imperial, polydomous, Russian-speaking. Book review: Shafranskaya, E.F., Garipova, G.T. & Keshfidinov, Sh.K. (2024). Transcultural literature of the XXI century. Moscow: Yurait Publ. (In Russ.) - Alexander G. Kovalenko; Valeria A. Chaurova (RUDN Journal of Studies in Literature and Journalism)
-